STUDENTS' AUTONOMOUS LEARNING IN FLIPPED CLASSROOM: THE ANALYSIS OF THE POTENTIALS AND PITFALLS - Lungguh Halira Vonti; Abdul Rosyid (UNIVERSITAS PAKUAN, 2022)
The use of technology in teaching has increased significantly and the conventional classroom now can be replaced by providing online teaching-learning. Most of the platforms of online learning focus only on giving assignments and works instead of giving teaching material. Thus, in the teaching and learning process, the students' autonomous learning are not built. In this study, flipped classrooms were the model of online learning used replacing the role of students and teachers in the teaching and learning process and to see how it affected the learners' autonomy. The flipped classroom approach stated to be a shift of the responsibility from teacher to students, thus the students were not passive participants in the classroom and they were given the opportunity to develop their own autonomy in learning. This study aimed to describe the potential and pitfalls of applying flipped classroom as a teaching model in the teaching and learning process. The researchers employed a qualitative research design and the data was collected through an interview and Learner Autonomy Questionnaire. The system logs used in flipped classrooms was also taken as a triangulation data.